Motor impulsivity and the ventrolateral prefrontal cortex - Maldonado, Roberto Goya; Walther, Stephan; Simon, Joe J.; Stippich, Christoph; Weisbrod, Matthias; Kaiser, Stefan (Psychiatry research. Neuroimaging, 2010)
Functional magnetic resonance imaging in a Go/Nogo task was employed to investigate the relationship between trait impulsivity and brain activation during motor response inhibition. We found a positive correlation between motor impulsivity and activation of bilateral ventrolateral prefrontal cortex during successful inhibitions, which suggests stronger recruitment to maintain task performance.
Gesehen am 28.04.2023